PEMIKIRAN EKONOMI SUBCHAN ZAENURI ECHSAN DI INDONESIA TAHUN 1953-1973 - Heryanto, Yayan Aom (2015)
This thesis is titled "The Economic Thinking of Subchan Zaenuri Echsan in Indonesia at 1953-1973." The main problem which is studied in this thesis is "How the Economic Thinking of Subchan Zaenuri Echsan in Indonesia at 1953-1973." These problems are divided into four research questions namely (1) What was the background which caused the economic thinking from Subchan Zaenuri Echsan towards economy concept in Indonesia in 1953 until 1973, (2) What was the economy concept from Subchan Zaenuri Echsan, (3) How the role of Subchan Zaenuri Echsan in implementing economic thinking in Indonesia at 1953 until 1973, (4) How the effect of Subchan Zaenuri Echsan economic thinking towards economy development in Indonesia from 1953 until 1973. Research method which is used is historical method, namely, source collection, source critiques, interpretation and historiography. The background of Subchan Zaenuri Echsan economic thinking was caused by economy condition and also government policies at that time which was not able to improve economy condition, especially, Indonesian people prosperity and democracy in economy sector was not achieved. In Old Order era, economy system which was used was Guided Economy. Guided Economy is a policy which emphasized the role of government in running economy in one country which was very dominant, it caused people involvement as economy actor was limited so it made people could not be creative and free in developing their own economy. Subchan Zaenuri Echsan economic thinking was made to improve economy condition and also people prosperity and democracy in economy sector. Economy of development was one way to improve prosperity of Indonesian people. Subchan Zaenuri Echsan implemented his economy thinking through national seminar about economy, which was realized by government in 1967. Besides, Subchan Zaenuri Echsan economic thinking was seen in the beginning of New Order era which began to improve and set the policies which is suitable with the economy condition at that time. It can be seen from economy policy which is used by New Order administration, which was more tend to economy development, infrastructure development and also people prosperity were become main priority. Nevertheless, in the practice there was inconsistency in implementing such policies, so, Subchan Zaenuri Echsan criticized the New Order administration policies which had distorted from initial goal --------- Skripsi ini berjudul "Pemikiran Ekonomi Subchan Zaenuri Echsan di Indonesia Tahun 1953-1973". Masalah utama yang diangkat dalam skripsi ini adalah "Bagaimana Pemikiran Ekonomi Subchan Zaenuri Echsan di Indonesia Tahun 1953-1973". Dari masalah utama tersebut dibagi menjadi empat pertanyaan penelitian, yaitu (1) Apa yang melatarbelakangi munculnya pemikiran Subchan Zaenuri Echsan terhadap konsep ekonomi di Indonesia pada tahun 1953 sampai 1973, (2) Apa konsep ekonomi Subchan Zaenuri Echsan, (3) Bagaimana peranan Subchan Zaenuri Echsan dalam mengimplementasikan pemikiran ekonomi di Indonesia pada tahun 1953 sampai 1973, (4) Bagaimana dampak dari pemikiran ekonomi Subchan Zaenuri Echsan terhadap perkembangan ekonomi di Indonesia pada tahun 1953 sampai 1973. Metode penelitian adalah metode historis yaitu pengumpulan sumber, kritik sumber, interpretasi dan historiografi. Latar belakang munculnya pemikiran ekonomi Subchan Zaenuri Echsan disebabkan oleh keadaan perekonomian serta kebijakan pemerintah pada saat itu tidak mampu memperbaiki keadaan, khususnya kesejahteraan rakyat Indonesia serta demokrasi di bidang ekonomi tidak tercapai. Pada masa pemerintahan Orde Lama diberlakukan kebijakan ekonomi yaitu Ekonomi Terpimpin. Ekonomi Terpimpin merupakan kebijakan yang menonjolkan peranan serta campur tangan pemerintah dalam menjalankan perekonomian sangat dominan, hal ini menyebabkan keterlibatan rakyat sebagai pelaku ekonomi terbatas sehingga membuat rakyat tidak dapat berkreasi dengan bebas dalam mengembangkan ekonominya sendiri. Pemikiran ekonomi Subchan Zaenuri Echsan muncul untuk memperbaiki keadaan perekonomian serta kesejahteraan rakyat dan demokrasi di bidang ekonomi. Ekonomi pembangunan merupakan salah satu cara untuk memperbaiki kesejahteraan rakyat Indonesia. Subchan Zaenuri Echsan mengilementasikan pemikiran ekonominya melalui seminar nasional ekonomi, yang selanjutnya direalisasikan pada tahun 1967 oleh pemerintah. Selain itu, pemikiran ekonomi Subchan Zaenuri Echsan diimplementasikan melalui ketetapan MPRS yaitu pada tahun 1966 dan 1968, dimana pada tahun tersebut Subchan Zaenuri Echsan merupakan salah satu Wakil Ketua MPRS. Dampak dari pemikiran ekonomi Subchan Zaenuri Echsan terlihat pada masa pemerintahan awal Orde Baru yang mulai berbenah dan menentukan kebijakan yang sesuai dengan keadaan ekonomi pada masa itu. Hal ini terlihat dari kebijakan ekonomi yang digunakan oleh pemerintahan Orde Baru, lebih kepada pembangunan ekonomi, sarana dan prasarana serta kesejahteraan rakyat di utamakan. Namun, dalam perjalanannya terjadi ketidak stabilan dalam melaksankan kebijakan tersebut, sehingga Subchan Zaenuri Echsan mengkritisi kebijakan pemerintahan Orde Baru yang telah menyimpang dari tujuan semula.